Cover Image. Issue 2 (13th April 2021) - Mpakou, Vassiliki; Spathis, Aris; Bouchla, Anthi; Tsakiraki, Zoi; Kontsioti, Frieda; Papageorgiou, Sotirios; Bazani, Efthymia; Gkontopoulos, Konstantinos; Thomopoulos, Thomas; Glezou, Irene; Galanopoulos, Athanasios; Symeonidis, Argiris; et al.
Abstract : The cover image depicts Anti‐Hif‐1a immunohistochemistry of BM biopsy sectionsfrom a 5‐AZA‐R patient, with high frequency of Hif‐1α (+) cells, and is based on the Original Article Upregulated Hif‐1α signaling pathway in high risk myelodysplastic syndrome and acute myeloid leukemia patients is associated with better response to 5‐azacytidine ‐ Data from the Hellenic MDS study group by Vassiliki Pappa et al., https://doi.org/10.1002/hon.2834 .